Anti-apolipoprotein A-1 IgG, incident cardiovascular events, and lipid paradox in rheumatoid arthritis - Mongin, Denis; Pagano, Sabrina; Lamacchia, Celine; Juillard, Catherine; Antinori-Malaspina, Paola; Dan, Diana; Ciurea, Adrian; Möller, Burkhard; Gabay, Cem; Finckh, Axel; Vuilleumier, Nicolas (Frontiers in Cardiovascular Medicine, 2024)
Objective. To validate the prognostic accuracy of anti-apolipoprotein A-1 IgG (AAA1) for incident major adverse cardiovascular (CV) events (MACE) in rheumatoid arthritis (RA) and study their associations with the lipid paradox at a multicentric scale.Baseline AAA1 IgG, lipid profile, atherogenic indexes, and cardiac biomarkers were measured on the serum of 1472 RA patients included in the prospective Swiss Clinical Quality Management registry with a median follow-up duration of 4.4 years. MACE was the primary endpoint defined as CV death, incident fatal or nonfatal stroke, or myocardial infarction (MI), while elective coronary revascularisation (ECR) was the secondary endpoint. Discriminant accuracy, and incidence rate ratios (IRR) were respectively assessed by C-statistics and Poisson regression models. Results. During follow-up, 2.4% (35/1472) patients had a MACE, consisting in 6 CV deaths, 11 MI and 18 strokes, and ECR occurred in 2.1% (31/1472) of patients. C-statistics indicated that AAA1 had a significant discriminant accuracy for incident MACE (C-statistics:0.60, 95%confidence intervals[95%CI]:0.57-0.98, p=0.03), mostly driven by CV deaths (C-statistics: 0.77; 95%CI: 0.57-0.98, p=0.01). IRR indicated that each unit of AAA1 IgG increase was associated with a 5-fold incident CV death rate, independently of models' adjustments. At the predefined and validated cut-off, AAA1 displayed negative predictive values above 97% for MACE. AAA1 inversely correlated with total, and HDL cholesterol. Conclusions. AAA1 independently predicts CV deaths, and marginally MACE in RA. Further investigations are requested to ascertain whether AAA1 could enhance CV risk stratification by identifying RA patients at low CV risk.